Phytomicrobiome communications: Novel implications for stress resistance in plants - Khanna, Kanika; Kohli, Sukhmeen Kaur; Sharma, Nandni; Kour, Jaspreet; Devi, Kamini; Bhardwaj, Tamanna; Dhiman, Shalini; Singh, Arun Dev; Sharma, Neerja; Sharma, Anket; Ohri, Puja; Bhardwaj, Renu; et al. (Frontiers in Microbiology, 2022)
Agricultural sector is a foremost contributing factor for supplying food at global scale. There are plethora of biotic as well as abiotic stressors that act as major constraints for agricultural sector in terms of global food demand, quality and security. Stresses affect rhizosphere and their communities, root growth, plant health and productivity. They also alter numerous plant physiological and metabolic processes. Moreover, they impact transcriptomic and metabolomic changes, causing alteration in root exudates and affecting microbial communities. Since the evolution of hazardous pesticides and fertilizers, productivity has experienced elevation but at the cost of impeding soil fertility thereby, causing environmental pollution. Therefore, it is crucial to develop sustainable and safe means for crop production. The emergence of various evidences depicting the alterations and abundance of microbes under stressed conditions proved to be beneficial and outstanding for maintaining plant legacy and stimulating their survival. Beneficial microbes offers a great potential for plant growth during stresses in an economical manner. Moreover, they promote plant growth with regulating phytohormones, nutrient acquisition, siderophore synthesis and induce antioxidant system. Besides, acquired or induced systemic resistance also counteracts biotic stresses. The phytomicrobiome exploration is crucial to determine the growth promoting traits, colonisation and protection of plants from adversities caused by stresses. Further, the inter-communications among rhizosphere through direct/indirect manner facilitate growth and form complex network. The phytomicrobiome communications are essential for promoting sustainable agriculture where microbes act as ecological engineers for environment. In the present review, we have reviewed our building knowledge regarding role of microbes in plant defense and stress-mediated alterations within the phytomicrobiomes. We have depicted the defense biome concept that infers the design of phytomicrobiome communities and their fundamental knowledge about plant-microbe interactions for developing plant probiotics.